Innovative Corporate Social Responsibility (CSR) Policies Based on Local Wisdom: Towards an Inclusive and Sustainable Development Model - Dimas Imaniar; Hadi Prayitno; Dina Suryawati; Wheny Khristianto (Smart Society, 2026)
Although Corporate Social Responsibility (CSR) has been widely adopted, most implementations in developing countries tend to be oriented towards regulatory compliance and biased towards the economic-environmental dimension. This approach often ignores local socio-cultural aspects, thus triggering low social legitimacy and program sustainability. To fill this gap, this study examines innovation in CSR policy through the integration of local wisdom values as the basis for inclusive and sustainable regional development. Using the theoretical framework of the Advocacy Coalition Framework (ACF) and Triple Bottom Line (TBL), this study employs a qualitative case study with an exploratory approach to analyze the dynamics of CSR policy in Banyuwangi Regency, Indonesia. Data were obtained through in-depth interviews with 15 key informants, document analysis, and field observations involving government actors, companies, and local communities. The results show that CSR policy in Banyuwangi has undergone a transformation from a philanthropic and regulatory approach to a participatory policy model rooted in local culture. This policy innovation is concretely realized through the institutionalization of the values of Gugur Gunung (collective work), Sambatan (mutual cooperation), and Tanggap ing Sasmita (social sensitivity) into the Regional Medium-Term Development Plan (RPJMD), orchestration of multi-actor coalitions in which local governments act as policy intermediaries, and transformation of programs into sustainable partnerships focused on empowering creative MSMEs and conserving green tourism. Theoretically, this study contributes by integrating ACF and TBL in the local cultural context to form a hybrid model of CSR policy innovation. Practically, the results offer strategic direction for local governments and companies in designing CSR programs that are socially just, sustainable, and responsive to local cultural values.